2021
DOI: 10.4251/wjgo.v13.i3.185
|View full text |Cite
|
Sign up to set email alerts
|

Should we resect colorectal cancer in patients over the age of 85?

Abstract: BACKGROUND The prevalence of colorectal cancer in the elderly is rising, with increasing numbers of older patients undergoing surgery. However, there is a paucity of information on the surgical outcomes and operative techniques used in this population. AIM To evaluate the post-operative outcomes for patients ≥ 85 years old following colorectal cancer resection as well as evaluating the outcomes of laparoscopic resection of colorectal cancer in patients over 85. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…While older studies have found that older patients have worse CRC surgical outcomes and survival than their younger counterparts[ 59 ], recent studies have shown otherwise[ 60 - 67 ]. Improvements in perioperative care, surgical techniques and the introduction of multimodal treatments have made surgery feasible for the majority of patients, including many older cancer patients[ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While older studies have found that older patients have worse CRC surgical outcomes and survival than their younger counterparts[ 59 ], recent studies have shown otherwise[ 60 - 67 ]. Improvements in perioperative care, surgical techniques and the introduction of multimodal treatments have made surgery feasible for the majority of patients, including many older cancer patients[ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…These have supported that minimally invasive surgery in older CRC patients reduces overall mortality and morbidity when compared to a laparotomy, and correlates with shorter hospital stays and faster functional recovery. Furthermore, it has been clearly demonstrated that postoperative outcomes in advanced age do not significantly differ from those of younger CRC patients[ 60 - 67 ]. One study found that intraoperative and postoperative complications were equally distributed among CRC patients over 75 years of age and younger patients[ 60 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The standard operability of each case was determined according to the Japanese guidelines for the treatment of stomach[ 12 - 14 ] and colorectal cancer[ 15 - 18 ]. Based on the clinical period and location of the cancer, each institution selects the appropriate surgical procedure and determines the scope of resection, including possible lymph node resection.…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, the number of elderly patients admitted to hospital for surgery has increased. This is particularly reported in colorectal surgery; indeed, the prevalence of 2 of 13 colorectal cancer (CRC) is rising among older adults [1]. Surgical outcomes could be hampered by a poor physical status.…”
Section: Introductionmentioning
confidence: 99%